2021
DOI: 10.1186/s12911-021-01605-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient connectivity with healthcare professionals and health insurer using digital health technologies during the COVID-19 pandemic: a German cross-sectional study

Abstract: Background Digital health technologies enable patients to make a personal contribution to the improvement of their health by enabling them to manage their health. In order to exploit the potential of digital health technologies, Internet-based networking between patients and health care providers is required. However, this networking and access to digital health technologies are less prevalent in sociodemographically deprived cohorts. The paper explores how the use of digital health technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Another option might have been to administer the card game as an online patient survey for the identification of patient-relevant (sub)criteria [24], by which risks associated with contact during the COVID-19 pandemic would have been limited, and the sample size potentially could have been increased. However, an online patient survey without interviewer assistance with this particular patient group-aged adults with cognitive impairments, oftentimes living in rural areas, which may have limited access to the internet and a lack of necessary digital literacy [89]-was deemed not feasible by the study team based on previous research [25] and experiences from other projects at the site [90]. As criteria-related questions and card games took longer than expected and most PlwD got tired, we could not show the sub-criteria cards and ask for feedback on their appropriateness and comprehensibility.…”
Section: Limitationsmentioning
confidence: 99%
“…Another option might have been to administer the card game as an online patient survey for the identification of patient-relevant (sub)criteria [24], by which risks associated with contact during the COVID-19 pandemic would have been limited, and the sample size potentially could have been increased. However, an online patient survey without interviewer assistance with this particular patient group-aged adults with cognitive impairments, oftentimes living in rural areas, which may have limited access to the internet and a lack of necessary digital literacy [89]-was deemed not feasible by the study team based on previous research [25] and experiences from other projects at the site [90]. As criteria-related questions and card games took longer than expected and most PlwD got tired, we could not show the sub-criteria cards and ask for feedback on their appropriateness and comprehensibility.…”
Section: Limitationsmentioning
confidence: 99%
“…Older adults and less educated people have been affected the most by lockdown measures [ 9 , 10 ]. Some hospitals have implemented mHealth-based online appointments and video consultations with health care providers [ 11 , 12 ], instead of traditional register windows and consultation rooms, in order to reduce contacts [ 13 , 14 ]. Vulnerable people benefit the least from these digital solutions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Becker et al concluded in their article that a valuable way to manage COVID-19 surges is virtual rounding [12]. Along a similar line, Hannemann et al found that digital health technologies can provide a platform to expand the offering of healthcare services [13]. Nonetheless, the authors also described that with the increasing reliance on technology, a digital divide stratified by sociodemographic and socioeconomic determinants became evident [13].…”
Section: Resultsmentioning
confidence: 99%